Social media and adoption. Issue 7 (2nd July 2021) - Harris, Alexandra Conroy
Abstract : Alexandra Conroy Harris, legal consultant at CoramBAAF, on how the ease of social media contact between adopted children and birth families is a challenge that could reset expectations for all parties